Endogamy costs and reproductive biology of Laelia autumnalis, an endemic orchid of Mexico - Emeterio-Lara, Aucencia; García-Franco, José G.; Hernández-Apolinar, Mariana; Mora-Herrera, Martha E.; Toledo-Hernández, Víctor H.; Valencia-Díaz, Susana; Flores-Palacios, Alejandro (Plant ecology, 2018)
It has been hypothesized that the fitness of selfed progeny must be lowered by inbreeding depression. Most research into the breeding systems of orchids shows a similar fruit set from outcrossing and self-pollination, but few studies have measured seed production and viability. In five populations of Laelia autumnalis, in central México, we studied the species reproductive system and the early costs of endogamy. We performed spontaneous self-pollination, apomixis, assisted self-pollination, cross-pollination, and exogamous pollination (using pollen from a different population) treatments of bagged flowers and measured fruit set, seed production, and germination No fruits were produced in the apomixis and spontaneous self-pollination treatments. Reproductive success from self-pollination was lower than that from cross-and exogamous pollination and no difference was found between the latter two treatments. The ratio between self-pollination and cross-pollination success in different traits ranged from 0.80 ± 0.18 (fruit set) to 0.22 ± 0.13 (seeds with embryo). The latter value suggests a high endogamy costs in the production of viable seeds. The concatenated success of the different traits studied showed that the relative fitness of selfpollination was 63% lower than with cross-pollination. Laelia autumnalis is a self-compatible nonautogamous species in which the cost of endogamy occurs at seed production and cannot be compensated for at other early stages. This also occurs in other orchid species and is likely to be a general pattern.